CÁC CHẤT HỖ TRỢ CHUYỂN HÓA (METABOLIC MODIFIERS) SỬ DỤNG TRONG CHĂN NUÔI - Beermann, Donald H.; Dunshea, Frank R. (Council for Agricultural Science and Technology (CAST), 2006)
This paper provides a discussion of metabolic modifiers–a group of compounds that alter the physiology and metabolism of animals in specific ways to improve efficiency of meat and milk production and, in certain instances, to improve yield and composition of animal-derived products.The paper describes the classification, characteristics, and effects of metabolic modifiers approved for use in animal production and presents the current status of metabolic modifier approval around the world.Topics include a brief history of this technology, applications, and contributions to animal agriculture.